2006
DOI: 10.1074/jbc.m512509200
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Deletion Leads to Up-regulation of a Secreted Growth Factor Pleiotrophin

Abstract: PTEN 4 (phosphatase and tensin homologue deleted on chromosome ten) is the first phosphatase identified as a tumor suppressor (1-3). Loss of function mutations or reduced expression of the PTEN gene are found at high frequencies in a wide variety of human tumors, including glioblastoma, as well as endometrial, prostate, colorectal, lung, and breast cancers. Experimental and clinical evidence demonstrate that PTEN is a critical tumor suppressor (4).PTEN acts primarily as a negative regulator of the phosphoinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 47 publications
2
18
1
1
Order By: Relevance
“…The observed neuroepithelial cell hyperplasia in Pten D/D mice is not caused by a cell autonomous mechanism, but is likely due to paracrine signaling from adjacent cells that are deficient in PTEN, consistent with previous studies in which epithelial cells that are adjacent to NEBs contribute to PNE cell hyperplasia (31). Deletion of PTEN in fibroblast and mammary tumor cells in vivo enhanced secretion of growth factors, including pleotrophin, that may influence cell adhesion, migration, survival, growth, and differentiation via a paracrine mechanism (50).…”
Section: Discussionsupporting
confidence: 71%
“…The observed neuroepithelial cell hyperplasia in Pten D/D mice is not caused by a cell autonomous mechanism, but is likely due to paracrine signaling from adjacent cells that are deficient in PTEN, consistent with previous studies in which epithelial cells that are adjacent to NEBs contribute to PNE cell hyperplasia (31). Deletion of PTEN in fibroblast and mammary tumor cells in vivo enhanced secretion of growth factors, including pleotrophin, that may influence cell adhesion, migration, survival, growth, and differentiation via a paracrine mechanism (50).…”
Section: Discussionsupporting
confidence: 71%
“…24,25 HP activates eNOS through activation of Akt, 26,27 which in the studied pathway lies down-stream of p38 (supplementary file 2) and has been also implicated in the regulation of PTN expression. 28 We have recently shown that NO mediates HP-induced angiogenesis in vivo 5 and endothelial cell migration in vitro. 6 The results of the present study suggest that this may be due to eNOS/ NO mediated PTN expression, which is also angiogenic in the same systems.…”
Section: Discussionmentioning
confidence: 99%
“…Both PTN and Wnt repress adipocyte differentiation through cytosolic accumulation and nuclear translocation of b-catenin, so it is possible that there is cross-talk between the Wnt and PTN signaling pathways during preadipocyte differentiation. To confirm our hypothesis, we searched for the molecule directly connected to both pathways and found GSK-3b [21,29]. Wnt signals through the frizzled receptor (Fz) and the low density lipoprotein receptor-related protein (LRP) co-receptors [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…As a growth factor, PTN stimulates mitogenesis of fibroblasts, endothelial cells, and epithelial cells in culture, as well as neurite outgrowth in neonatal neuronal cells [10,15,16]. As a potent proto-oncogene, a ratelimiting angiogenic factor during tumor growth, and a potential tumor promoter, PTN transforms NIH 3T3 cells and is highly expressed in various tumor cell lines and tumor tissues, such as in breast cancer, melanoma, pancreatic cancer, prostate cancer, and colon cancer [17][18][19][20][21]. PTN also induces differentiation of oligodendrocyte progenitors and regulates branching morphogenesis of the ureteric bud during development of the kidney [4,22].…”
Section: Introductionmentioning
confidence: 99%